Single-phase binary phase-shift keying, quadrature phase shift keying demodulators using an XOR gate as a phase detector - Kaewmunee, Apinut; Khumsat, Phanumas (Institute of Advanced Engineering and Science, 2023)
A single-phase/single-loop multiple-phase-shift-keying (m-PSK) demodulator is described. The demodulator relies on a linear range of an exclusive-OR (XOR) gate employed as a phase detector. The phase controller takes the average output from the XOR gate and performs a sub-ranging/re-scaling operation to provide an input signal to a voltage-controlled oscillator (VCO). The demodulator is truly modular which theoretically can be extended for an m-PSK signal. The proposed single-phase binary-/quadrature-PSK (BPSK/QPSK) demodulators have been implemented with low-cost discrete components. The core of the phase controller simply relies on number of stages of a full-wave rectifier and a linear amplifier built from well-known op-amp-based negative feedback circuits. The demodulator prototypes operate from a single supply of 5 V. At a carrier frequency of 100 kHz, both the BPSK and QPSK demodulators achieved the maximum symbol rate of 20 ksymbol/s respectively. At these symbol rates, the BPSK and QPSK demodulators deliver symbol-error rates less than 2×10-10 and 7×10-10.